2016
DOI: 10.1038/srep23281
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric analysis of accumulated TDP-43 in amyotrophic lateral sclerosis brains

Abstract: TDP-43 is the major disease-associated protein involved in the pathogenesis and progression of amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration with ubiquitin-positive inclusions linked to TDP-43 pathology (FTLD-TDP). Abnormal phosphorylation, truncation and cytoplasmic mis-localization are known to be the characteristics for the aggregated forms of TDP-43, and gain of toxic abnormal TDP-43 or loss of function of physiological TDP-43 have been suggested as the cause of neurodegeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
133
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(141 citation statements)
references
References 51 publications
6
133
1
1
Order By: Relevance
“…Indeed, based on the similarities of the characteristic bands in SDS-PAGE chromatograms previously described (Nonaka et al, 2013; Kametani et al, 2016), our conformer may represent the structural core of Type A TDP-43 proteinopathy, the most common class of TDP-43 maladies (Mackenzie et al, 2011). As TDP-43 Type A aggregates are remarkably more heat-stable as seeds than Type B or Type C aggregates (Nonaka et al, 2013), what remains to be addressed is the basis of this exceptional stability.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…Indeed, based on the similarities of the characteristic bands in SDS-PAGE chromatograms previously described (Nonaka et al, 2013; Kametani et al, 2016), our conformer may represent the structural core of Type A TDP-43 proteinopathy, the most common class of TDP-43 maladies (Mackenzie et al, 2011). As TDP-43 Type A aggregates are remarkably more heat-stable as seeds than Type B or Type C aggregates (Nonaka et al, 2013), what remains to be addressed is the basis of this exceptional stability.…”
Section: Introductionmentioning
confidence: 73%
“…Based on the apparent protection of residues 341–367 against Ser phosphorylation, Gln/Asn deamidation and Met oxidation in TDP-43 ex vivo aggregates, we therefore propose as a working hypothesis that our conformational model for this segment (Figure 2) may correspond to the pathological conformer present in the ex vivo aggregates of patient 2 described by Kametani et al (2016). Indeed, based on the similarities of the characteristic bands in SDS-PAGE chromatograms previously described (Nonaka et al, 2013; Kametani et al, 2016), our conformer may represent the structural core of Type A TDP-43 proteinopathy, the most common class of TDP-43 maladies (Mackenzie et al, 2011).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Interestingly, the C-terminal fragment-banding patterns of converted host proteins resemble those of insoluble TDP-43 used as seeds, suggesting that the conversion is template-dependent. Moreover, mass spectrometric analysis of insoluble TDP-43 from brains of ALS patients suggested that RRM2, the glycine-rich domain, and a part of the Q/N-rich domain form the core region of TDP-43 aggregates 23 . These results suggest that seed-dependent accumulation of prion-like, conformationally changed TDP-43 via interaction at the C-terminal region has a pivotal role in the pathogenesis of ALS and FTLD-TDP.…”
mentioning
confidence: 92%